From Precarity to Divine Sufficiency: A Qur’anic Response to the Neoliberal Structuring of Marriage Delay - Bakar, Abu; Maram, Ahmad Nabilul; Rozaq, Muhammad Fathur; Ulum, Muhammad Nashrul (KALAM, 2026)
The increasing tendency among Muslim youth to delay marriage reflects a growing tension between the Qur’anic promise of divine sufficiency and the economic insecurity produced by contemporary neoliberal conditions. Existing studies tend to examine this issue either sociologically or exegetically, leaving limited attention to an integrated theological framework that addresses structural economic precarity. This study employs Fazlur Rahman’s Double Movement theory to reinterpret classical Qur’anic exegeses by reconstructing their original moral vision and contextualizing it within contemporary socioeconomic realities. The study finds that classical Islamic hermeneutics dissociate the legitimacy of marriage from material accumulation, emphasizing spiritual sufficiency and ethical responsibility over market-oriented financial standards. This article proposes a “responsive marital theology” that redefines qanāʿah (contentment) not as passive resignation, but as an active ethical framework for social resilience. By repositioning marriage as a collective social responsibility (farḍ kifāyah), the study offers a theological foundation for institutional and community-based interventions aimed at reducing structural barriers to marriage in contemporary Muslim societies. [Meningkatnya kecenderungan menunda pernikahan di kalangan pemuda Muslim mencerminkan ketegangan antara janji al-Qur’an tentang kecukupan ilahi dan ketidakamanan ekonomi yang dihasilkan oleh kondisi neoliberal kontemporer. Kajian-kajian sebelumnya cenderung membahas persoalan ini secara sosiologis atau eksegetis secara terpisah, sehingga masih terbatas perhatian terhadap kerangka teologis integratif yang mampu menjelaskan problem ketidakpastian ekonomi struktural. Penelitian ini menggunakan teori Double Movement Fazlur Rahman untuk menafsirkan kembali tafsir-tafsir klasik al-Qur’an melalui rekonstruksi visi moral dasarnya dan kontekstualisasinya dalam realitas sosial-ekonomi kontemporer. Hasil penelitian menunjukkan bahwa hermeneutika Islam klasik memisahkan legitimasi pernikahan dari akumulasi material dengan menekankan kecukupan spiritual dan tanggung jawab etis di atas standar finansial yang berorientasi pasar. Artikel ini menawarkan konsep “teologi pernikahan responsif” yang mendefinisikan ulang qanā‘ah bukan sebagai bentuk kepasrahan pasif, melainkan sebagai kerangka etis aktif bagi ketahanan sosial. Dengan menempatkan kembali pernikahan sebagai tanggung jawab sosial kolektif (farḍ kifāyah), penelitian ini memberikan landasan teologis bagi intervensi institusional dan berbasis komunitas untuk mengurangi hambatan struktural terhadap pernikahan dalam masyarakat Muslim kontemporer.]